La quête de reconnaissance dans la socialisation de garçons et d’adolescents martiniquais - Joëlle Kabile (Amnis)
This paper questions the recognition arrangements that are available to boys and young men in male socialization in Martinican society. The latter, often based on authoritarian modes of education, complicates the valuation and recognition but does not exclude them either. The importance of the recognition by the peers group is fundamental but also exposes individuals to contempt and ambivalence.